SIMULASI DAN PERENCANAAN STATION KEEPING SATELIT LAPAN-A4 (SSO) DENGAN MENGGUNAKAN PROPULSI NON-IMPULSIF - Rizki Zuhri, Muhammad
Sun-synchronous orbit is an orbit so that the satellite passes over certain region on Earth’s surface at the same local time every day. In order to achieve sun-synchronous orbit, the orbit has to have certain value of nodal precession rate, that is equal to 360°/year. This nodal precession rate is affected by some orbital parameters, those are eccentricity, semi major-axis, and inclination. Satellites using sun-synchronous orbit are mostly a LEO (Low-Earth Orbit) satellite, hence the orbit perturbation caused by the oblateness of Earth’s shape and atmospheric drag will be greater. These perturbations will affect to the changes of some orbital parameters value. As consequence, the value of nodal precession rate may change too, so its value is no longer 360°/year as expected for sun-synchronous orbit. Thus, the local time of the satellite will change too, so it needs to be corrected by some correction maneuvers. On this writing, the author studies about station keeping planning for sun-synchronous orbit by using inclination correction maneuver. The study is an analysis by simulation using GMAT with non-impulsive propulsion approach. On this research, LAPAN-A4 satellite, a satellite that is planned to be launched in 2020, is chosen to be the satellite that will be simulated. Station keeping planning for LAPAN-A4 satellite will be conducted by simulating some alternative plannings of inclination correction maneuver based on periods ; maneuver for each 2 months, maneuver for each 4 months, maneuver for each 6 months, maneuver for each 12 months, and maneuver for each 24 months,. The simulation results show that the optimal station keeping planning is maneuver for each 2 months. This alternative shows the lowest fuel consumption, so that the fuel and launch cost will be minimum, and the local time drift that is still may be tolerated.